Miejsce człowieka w koncepcji czasu Michaiła Osorgina - Murawski, Antoni (Studia Rossica Posnaniensia, 2012)
The main subject of the article is the way Mikhail Osorgin perceives the relation between man and time in his emigration novels. The category of time in Osorgin’s works cannot be considered apart from the human factor. Osorgin has always been interested in man’s role and place in the eternal stream of time.